2020
DOI: 10.1186/s12890-020-1054-9
|View full text |Cite
|
Sign up to set email alerts
|

CD248 and integrin alpha-8 are candidate markers for differentiating lung fibroblast subtypes

Abstract: Background: Lung fibrosis is a serious life-threatening condition whose manifestation varies according to the localization and characteristics of fibroblasts, which are considered heterogeneous. Therefore, to better understand the pathology and improve diagnosis and treatment of this disease, it is necessary to elucidate the nature of this heterogeneity and identify markers for the accurate classification of human lung fibroblast subtypes. Methods: We characterized distinct mouse lung fibroblast subpopulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…For example, Fig 4 shows significantly greater growth (as total spheroid area and number) in 0 μM than in 10 μM erlotinib. [37]. This aggregation is…”
Section: Growth Characterization and Properties Of Long-term Culturesmentioning
confidence: 87%
“…For example, Fig 4 shows significantly greater growth (as total spheroid area and number) in 0 μM than in 10 μM erlotinib. [37]. This aggregation is…”
Section: Growth Characterization and Properties Of Long-term Culturesmentioning
confidence: 87%
“…There was no significant difference in either DFS (p = 0.925) or OS (p = 0.492) between αSMA-high/FAPα-low and αSMA-low/FAPα-high groups ( Figure 3D,E). We also performed an analysis using markers CD248 and ITGA8, which were reported as markers to distinguish lung fibroblast subtypes [12], and there was also no significant survival difference ( Figure S1). Given these results that failed to reproduce those of previous studies, we concluded that fibroblast subtypes were indistinguishable when utilizing the gene expressions of fibroblast surface markers in PDAC bulk tumors alone.…”
Section: Fibroblast Subtypes In Pdac Are Indistinguishable By Transcrmentioning
confidence: 92%
“…surrounding vasculature) and vital in the regulation of tissue remodeling and homeostasis. The BMP7+ population had genes involved in myofibroblast differentiation, epithelial mesenchymal transition (EMT) and in TGFβ1-WNT signaling (PRSS23, ITGA8, BMP7, ITM2A and ARHGAP29) (15)(16)(17)(18). We hypothesize these three stromal clusters (ACTA+, ECM and BMP7+) represent stromal subtypes active in ECM breakdown, remodeling and organization which are important processes during proliferation, tissue repair and regeneration occurring in the endometrium, during, and after menstruation.…”
Section: Heterogeneity In the Endometrial Stromal Compartment And Posmentioning
confidence: 99%